Behavioral and neurobiological correlates of disturbed emotion processing in borderline personality disorder - Bertsch, Katja; Spieß, Karen; Herpertz, Sabine (Psychopathology, 2018)
One of the core symptoms of borderline personality disorder (BPD) is emotion dysregulation, which comprises emotion sensitivity, heightened and labile negative affect, deficient appropriate regulation strategies, and a surplus of maladaptive regulation strategies. Although earlier studies provided some evidence for threat hypersensitivity in terms of a negatively biased perception of other people (“negativity bias”) and deficits in the recognition of full-blown anger, i.e., higher error rates and slower reaction times, researchers have only recently started studying effects of interindividual differences (e.g., sex, impulsivity, aggressiveness) and stimulus complexity as well as associations with early adversity, developmental aspects, or the specificity for BPD. Recent data also suggest a deficit in the detection of positive emotions, which needs to be addressed in more detail since it may prevent the patients from recognizing safety signals and from making positive interpersonal experiences. Neurobiologically, threat hypersensitivity has been related to increased and prolonged amygdala responses, while deficient emotion regulation was associated with reduced prefrontal inhibition of the amygdala. First results suggest that these neural alterations may be modulated by psychotherapeutic treatment focusing on emotion regulation.